Pax 8 Prophecy Of Insilico Structure And Its Drug Interactio - Dr. ANNIDABALAKRISHNAN (International Journal of Pharma and Bio Sciences, 2012)
Pax genes encode a family of transcription factors that have been conserved through evolution and play different roles in early development. It is defined as a highly conserved motif of 128 amino acids, the paired-domain, which do not have any obvious sequence homology with other known protein domains. The present study investigates the PAX 8 prophecy of insilico structure and its drug interaction. Using the search tools such as NCBI, Pub med, Blast, Protein Data Bank, PDB etc., structural modeling can be done. Resulted study shows that in the absence of the three dimensional structures for most of the sequenced protein, homology modeling forms the basis for the resolution of the structure experimentally. Knowledge of the three dimensional structure of the homologous protein to the target sequence forms the pre requisite for insilico modeling. Structure validation results show that the quality of the predicted protein model is extremely good. Resulted data shows the energy value from anolea was found to be 0.3A0 Indicating a minimum deviation. Hence an interaction study indicates that the drug axitinib reacts with the protein PAX8 with least estimated fitness of – 103.533 and forms 4 hydrogen bonds with active site residues.